2021
DOI: 10.3390/nu13082653
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Anti-Inflammatory Protective Properties of Human Enriched Serum Following Artichoke Leaf Extract Absorption: Results from an Innovative Ex Vivo Clinical Trial

Abstract: The aging of our population is accompanied by an increased prevalence of chronic diseases. Among those, liver, joint and adipose tissue-related pathologies have a major socio-economic impact. They share common origins as they result from a dysregulation of the inflammatory and metabolic status. Plant-derived nutrients and especially polyphenols, exert a large range of beneficial effects in the prevention of chronic diseases but require clinically validated approaches for optimized care management. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
(77 reference statements)
0
21
0
1
Order By: Relevance
“…15 Artichoke leaf extract used in current study because it has an antioxidant that is accelerate healing by increased cell division, 16 also Artichoke oil has an anti-microbial effect due to phenolic contant, 17 anti-inflammatory effect that is important to prevent inflammation further more accelerate healing. 18 The current study showed that blood vessel formation is more accelerated in the experimental group than the control group due to the stimulation and the improvement of endothelial cells growth by using artichoke oil 19 and the antioxidant effect due to the phenolic content. 17 Present study revealed that the trabecular bone formation was more accelerated in artichoke oil group than the control group because of the artichoke oil anti-inflammatory effect due to its polyphenolic and the verbascoside compounds that had been reported in many reports to show a potential spectrum of several activities including anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 58%
“…15 Artichoke leaf extract used in current study because it has an antioxidant that is accelerate healing by increased cell division, 16 also Artichoke oil has an anti-microbial effect due to phenolic contant, 17 anti-inflammatory effect that is important to prevent inflammation further more accelerate healing. 18 The current study showed that blood vessel formation is more accelerated in the experimental group than the control group due to the stimulation and the improvement of endothelial cells growth by using artichoke oil 19 and the antioxidant effect due to the phenolic content. 17 Present study revealed that the trabecular bone formation was more accelerated in artichoke oil group than the control group because of the artichoke oil anti-inflammatory effect due to its polyphenolic and the verbascoside compounds that had been reported in many reports to show a potential spectrum of several activities including anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 58%
“…The human ex vivo methodology used in this study has been registered as a written invention disclosure by the French National Institute for Agronomic, Food and Environment Research (INRAE) (DIRV#18-0058). Clinic’n’Cell ® has been registered as a mark [ 24 , 25 , 26 , 27 ].…”
Section: Patentsmentioning
confidence: 99%
“…To address this knowledge gap and contribute to the determination of saffron’s mechanisms of action in humans, we designed an ex vivo clinical protocol based on human serum enrichment. The robustness of this pioneering approach was recently validated and published [ 24 , 25 , 26 , 27 ]. In this study, we combined human metabolism and cell cultures to try to understand whether and how circulating metabolites resulting from saffron extract consumption in humans may influence the activity of human neurons in the context of the oxidative stress commonly found in depression.…”
Section: Introductionmentioning
confidence: 99%
“…The human ex vivo methodology used in this study has been registered as a written invention disclosure by the French National Institute for Agronomic, Food and Environment Research (INRAE) (DIRV#18-0058). Clinic’n’Cell ® has been registered as a brand [ 16 , 30 , 31 , 32 , 33 ].…”
Section: Patentsmentioning
confidence: 99%
“…Using an ex vivo clinical approach developed at the French National Institute for Agronomic and Food Research (INRAE) [ 16 , 30 , 31 , 32 , 33 ], which considers the clinical digestive course of nutrients, we investigated the potential health benefits of the circulating metabolites following FCH ingestion in humans. In this light, we examined whether and how these human metabolites may influence major molecular protagonists responsible for skin hydration and remodeling.…”
Section: Introductionmentioning
confidence: 99%